Evaluation of the Formate Dehydrogenase Activity of Three‐Legged Pianostool Complexes in Dilute Aqueous Solution. Issue 34 (5th November 2014) - Keller, Sascha G.; Ringenberg, Mark R.; Häussinger, Daniel; Ward, Thomas R.
Abstract: Formic acid is an attractive means to reversibly store dihydrogen. In this context, d 6 pianostool complexes rank among the most‐effective formate dehydrogenase catalysts. With biologically generated formic acid in mind, we evaluated the performances of iridium‐based pianostool complexes bearing a cooperative ligand, which are known to catalyze formate decomposition. Interestingly, the phenylpyrazole‐derived catalyst [Cp*Ir(phenpz)(OH2 )] + (7, Cp* = pentamethylcyclopentadienyl, phenpz = 1‐phenylpyrazole) compares favourably with the very best systems [Cp*Ir(phenpzCO2 H)H2 O] + [8, phenpzCO2 H = 4‐(pyrazol‐1‐yl)benzoic acid] and [Cp*Ir(imim)H2 O] 2+ [11, imim = 2, 2′‐bis(4, 5‐dimethylimidazole)]. These catalysts display remarkable air tolerance, recyclability and activity under dilute aqueous conditions. Abstract : The catalytic activity of d 6 Ir pianostool complexes for formic acid decomposition was evaluated under dilute conditions. Both [Cp*Ir{phenpz(CO2 H)}H2 O] + (Cp* = pentamethylcyclopentadienyl, phenpz = 1‐phenylpyrazole) and [Cp*Ir(imim)H2 O] 2+ [imim = 2, 2′‐bis(4, 5‐dimethylimidazole)] display excellent activity, recyclability and air tolerance under the tested conditions.